EXPLORING THE IMPACT OF INTERNET ADDICTION AND ANXIETY ON MATHEMATICS ACHIEVEMENT IN SENIOR SECONDARY SCHOOL STUDENTS: A STUDY OF FOCUSED STUDY HABIT DISTRACTERS - Swati; Rathee, Neeru (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This exploratory study investigates the relationship between focused study habit distractors, specifically internet addiction and anxiety, and mathematics achievement among senior secondary school students. A sample of 800 students from senior secondary schools in Rohtak town participated in the study. The results reveal a significant negative correlation between internet addiction and mathematics achievement. However, no significant effect of anxiety on mathematics achievement was found. The study highlights the importance of addressing internet addiction and promoting healthy study habits to improve academic outcomes in mathematics. The findings have implications for educational practice, policy, and future research aimed at supporting students’ academic success.